A classification scheme for African production systems and its use for research resource allocation, program design and project monitoring - Boer, A.J. de (International Livestock Centre for Africa, 1977)
Classification system for livestock production systems in Africa, with particular reference to its use in ILCA's research activities spec. for research resources allocation, programme design and project monitoring.